The impact of urban business environment on the agglomeration of high-skilled labor - Liang, Jiawei; Yang, Di; Bo, Le (Asian Journal of Economics and Empirical Research, 2025)
In the era of technology-driven global economic transition, optimizing high-level labor agglomeration is crucial for economic growth as high-skilled workers prioritize urban business environments over housing prices and wages. Leveraging panel data from 280 Chinese cities spanning 2009-2021, this study delves into the impact of the urban business environment on high-skilled labor agglomeration. Specifically, the entropy weight method is employed to measure business environment indicators, and the location quotient is used to measure the level of high-skilled labor agglomeration. Employing two-way fixed effect, mediating effect, and threshold effect models, we find that improving the urban business environment significantly boosts high-skilled labor agglomeration, partially through enhanced urban innovation. However, the impact of the business environment on high-skilled labor agglomeration is constrained by the average wage level. If the average wage level is too low, the optimization of the urban business environment will impede the agglomeration of high-skilled labor. Our findings emphasize the importance of a favorable business environment and reasonable wage policies in attracting talent for sustainable economic development.